Transcriptionally active genome regions are preferred targets for retrovirus integration. - Scherdin, U (1990)
We have analyzed the transcriptional activity of cellular target sequences for Moloney murine leukemia virus integration in mouse fibroblasts. At least five of the nine random, unselected integration target sequences studied showed direct evidence for transcriptional activity by hybridization to nuclear run-on transcripts prepared from uninfected cells. At least four of the sequences contained multiple recognition sites for several restriction enzymes that cut preferentially in CpG-rich islands, indicating integration into 5' or 3' ends or flanking regions of genes. Assuming that only a minor fraction (less than 20%) of the genome is transcribed in mammalian cells, we calculated the probability that this association of retroviral integration sites with transcribed sequences is due to chance to be very low (1.6 x 10(-2]. Thus, our results strongly suggest that transcriptionally active genome regions are preferred targets for retrovirus integration.